2023
DOI: 10.3390/plants12091792
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Abiotic Stresses from Drought, Temperature, and Density on Germination and Seedling Growth of Barley (Hordeum vulgare L.)

Abstract: Seed germination and seedling growth are highly sensitive to deficit moisture and temperature stress. This study was designed to investigate barley (Hordeum vulgare L.) seeds’ germination and seedling growth under conditions of abiotic stresses. Constant temperature levels of 5, 10, 15, 20, 25, 30, and 35 °C were used for the germination test. Drought and waterlogging stresses using 30 different water levels were examined using two methods: either based at 1 milliliter intervals or, on the other hand, as perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…In 2021, the germination phase experienced cold temperatures, with recorded values of -1.12°C for the mean minimal temperature and 11.48°C for the mean temperature, in contrast to the milder conditions of 0.89°C and 12.9°C in 2022. Research conducted by Tarnawa et al, 42 has confirmed that lower temperatures have a detrimental effect on the germination of barley seeds. Additionally, it's worth noting that in 2021, the cultivated variety was Najah, whereas in 2022, it was Amalou.…”
Section: Discussionmentioning
confidence: 93%
“…In 2021, the germination phase experienced cold temperatures, with recorded values of -1.12°C for the mean minimal temperature and 11.48°C for the mean temperature, in contrast to the milder conditions of 0.89°C and 12.9°C in 2022. Research conducted by Tarnawa et al, 42 has confirmed that lower temperatures have a detrimental effect on the germination of barley seeds. Additionally, it's worth noting that in 2021, the cultivated variety was Najah, whereas in 2022, it was Amalou.…”
Section: Discussionmentioning
confidence: 93%
“…Barley seeds during germination require less water (48-65% of the grain weight) than seeds of other varnishes. After germination, due to the poor development of the root system, it requires a large amount of moisture [8,9]. The maximum amount of water of the plant is dissipated walk in the tillering -booting phase.…”
Section: Biological Features Of Barleymentioning
confidence: 99%
“…Drought and salinity stresses often occur during the early growth stages of plants, which are critical for determining their final yield and quality. Therefore, understanding the responses of plants to abiotic stress at this stage is essential for developing effective strategies to enhance crop resilience and adaptation ( Tarnawa et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%